Subacute exposure to inorganic mercuric chloride (HgCI2) induce testicular toxicity in rats - PRAKASH, N; RAMKRlSHNA, V; PAWAR, ASHOK (The Indian Journal of Animal Sciences, 2013)
Investigation was carried out to determine the nature of testicular toxicity following subacute exposure to inorganic mercuric chloride (HgCI2) in rats. Adult male Albino rats were divided into 3 groups each consisting of 8 animals. Group I served as untreated control, group 2 were exposed to inorganic HgCl2 5 PPM through drinking water for 13 weeks. Group 3 animals served as recovery group following treatment similar to group 2. Body weight and haematocrit values were monitored at regular intervals. On sacrification, testis were removed and weighed and subjected to histopathological examination along with liver and kidney tissue samples. Testicular weight of rats exposed to inorganic HgCl2 (groups 2 and 3) signiticantly (P<0.05) differed over control. The peritubular haemorrhage in the medullary region was evident in sections from kidney. Haematocrit values in treated rats were not different from untreated control group except for marginal decline in red blood cell count in group 2 and 3. The terminal testicular weights of HgCI2-treated rats wcre significantly (P<0.05) different from contro) The histopathological changes within the testis were mainly confined to Sertoti cells in group 2. The histotoxicological changes include discontinuation in basal lamina, vacuolation at multiple sites and disruption of spermatogenic cycle. The loss of architecture of testis was restored following a rest period. To conclude, subacute exposure to inorganic HgCI2 (5 PPM) induce reversible testicular toxicity in rats.